Haploinsufficiency of PRRT2 Leading to Familial Hemiplegic Migraine in Chromosome 16p11.2 Deletion Syndrome - Sen, Kuntal; Genser, Ilyse; DiFazio, Marc; DiSabella, Marc (Neuropediatrics, 2022)
Microdeletion in the 16p11.2 loci lead to a distinct neurodevelopmental disorder with intellectual disability and autism spectrum disorder in addition to dysmorphia, macrocephaly, and increased body mass index. One of the deleted genes in this region is PRRT2 which codes for proline-rich transmembrane protein 2. Heterozygous variants in PRRT2 cause four distinct neurological disorders including benign familial infantile epilepsy (BFIE), paroxysmal kinesigenic dyskinesia (PKD), PKD with infantile convulsions, and familial hemiplegic migraine (FHM). A 13-year-old male with a known history of 16p11.2 deletion and resultant cognitive delay presented with sudden onset of headache, left-sided weakness, facial droop, and aphasia concerning for acute ischemic stroke. Magnetic resonance imaging of the brain was performed urgently which did not reveal any acute processes and his presentation met criteria for hemiplegic migraine. There have been reports of PKD and BFIE in this microdeletion syndrome; however, our proband is the first case that presented with FHM related to haploinsufficiency of PRRT2. This report highlights the importance of counseling patient families regarding acute paroxysmal presentations in this syndrome.
Keywords: chromosome 16p11.2 deletion; PRRT2; familial hemiplegic migraine